On the Performance of Image Transmission in an Indoor Visible Light Communication System - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2024)
This study evaluates the performance of different modulation techniques, such as On-Off Keying (OOK), Amplitude Shift Keying (ASK) and Orthogonal Frequency Division Multiplexing (OFDM) in an Indoor Visible Light Communication (VLC) system for image transmission using the Line of Sight (LOS) transmission channel. Metrics such as Bit Error Rate (BER), data transmission rate, and latency are investigated as the Signal-to-Noise Ratio (SNR) and transmission distance functions. The results indicate that OOK and ASK are suitable for transmitting less demanding images in noisy environments. At the same time, OFDM offers better performance with its high transmission rate and low latency, making it ideal for rapidly transferring High-Definition (HD) images. © 2024 IEEE.